Qualitative evaluation of swimming technique to international spanisch junior and pre-junior swimmers: An analysis of error frequencies - Arellano, R.; Sanchez-Molina, J. A. (coachesinfo.com, 2002)
INTRODUCTION This study is a compilation of the analyses developed over four years of the Spanish Junior National Team during did the summer training camp (three weeks taper) before their participation at the European Junior Championships. The purpose of this study is to determine the frequency of observed mistakes while swimming freestyle. METHODS Subjects: A total of 177 swimmers of junior and pre-junior categories were analysed in a four-year period. Method: The swimmers were video-recorded through an underwater window (frontal and sagital views) while performing a freestyle 50-m trial at competitive speed. RESULTS Sixty-seven percent of the total group performed the arm pull with the elbow dropped and we did not find statistical differences between genders. 60% of the swimmers showed asymmetric stroke synchronisation. 45% of the male group and 74% of the female group pulled with the hand not crossing the sagital plane. 54% of the swimmers made the arm entry with the elbow extended while a 53% performed an anticipated shoulder and head rotation before breathing. DISCUSSION The high frequency values obtained in our study (averages more than 50%) for the five most repeated stroke mistakes demonstrates a lack of technical training in the age-group training programmes developed in Spain. Considering that the swimmers analysed were the best junior and pre-junior swimmers in our country would be an even greater probability to find higher mistake frequencies in the rest of the same age-group swimmers in the country. A more specific technical training plus a specific strength and flexibility development seems the way for the Spanish age-group coaches to improve the situation. (Abstract from the World Swimming Science Congress 2002)